Assessment of factor VIII gene in haemophilia a patients in east coast Malaysia - Mustaffa, Rapiaah; Isa, Nizam; Ibrahim, Illuni Hayati (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2004)
A study was initiated to amplify by PCR.